Self-assembled PCBM bilayers on graphene and HOPG examined by AFM and STM. (8th March 2018) - Li, Yanlong; Chen, Chuanhui; Burton, John; Park, Kyungwha; Heflin, James R; Tao, Chenggang
Abstract: In this work we report fabrication and characterization of phenyl-C61-butyric acid methyl ester (PCBM) bilayer structures on graphene and highly oriented pyrolytic graphite (HOPG). Through careful control of the PCBM solution concentration (from 0.1 to 2 mg ml −1 ) and the deposition conditions, we demonstrate that PCBM molecules self-assemble into bilayer structures on graphene and HOPG substrates. Interestingly, the PCBM bilayers are formed with two distinct heights on HOPG, but only one unique representative height on graphene. At elevated annealing temperatures, edge diffusion allows neighboring vacancies to merge into a more ordered structure. This is, to the best of our knowledge, the first experimental realization of PCBM bilayer structures on graphene. This work could provide valuable insight into fabrication of new hybrid, ordered structures for applications to organic solar cells.